PERAN PEMUDA DALAM PEMBANGUNAN SEKTOR PERIKANAN MARIKULTUR DI TELUK AMBON DALAM - Ongen Rumaryo Lekirupy; Johanis Hiariey; Yoisye Lopulalan (Universitas Pattimura, 2020)
Building the mariculture fisheries sector in Ambon can be an effort to build the regional economy. Cultivated fisheries other than capture fisheries are an economic driver because Indonesia is one of the world's fish sources, so the development of marine and fisheries aims to meet the needs of the international market. In developing the mariculture fisheries sector, youth participation is very necessary. Youth is very decisive in determining the progress and decline of development, but in reality, the youth now lacks awareness and willingness to be involved in development. Partial Least Square in Structural Equation Modeling with SmartPLS 3.0 software was used in this study to predict the effect of the exogenous latent variable X (factors determining the role of youth) to the endogenous latent variable Y (forms of the role of youth in the development of the mariculture fisheries sector) and describes the theoretical relationship between the two variables. SEM_PLS analysis results show that, resources have a significant effect on because the resources owned by youth are quite adequate. Social capital has a less significant effect because some youth are beginners. Public policies have a less significant effect because generally policies are directed at business managers who have succeeded in production so that young youth are less targeted for policy implementation. Entrepreneurship has a less significant effect because youth are still dominantly involved as members of business and labor groups so that not many have taken on the role of manager of floating net cage businesses.